Presenting a Model of Deficiencies and Governance Problems in the Banking System - Mohammadi, Masoud; Kazemi, Hossein; Rezaei, Farzin (Business, Marketing, and Finance Open, 2025)
Corporate governance in Iran’s banking system holds significant importance, as it plays a vital role in ensuring the sound and transparent functioning of banks. However, the Iranian banking system faces various challenges in the areas of management, supervision, and transparency, which can negatively affect public trust and the efficiency of these institutions. This article investigates the current state of corporate governance in Iranian banks and offers strategies for its improvement. The present study is applied in terms of its objective and follows a mixed-method research design in terms of methodology and data collection. The statistical population in the qualitative section includes 15 experts, comprising bank managers and faculty members. The primary data collection instrument is a semi-structured interview (in the qualitative section). In this study, after coding the interview transcripts, synonymous and frequently repeated criteria were removed, and the final criteria were categorized and classified. As a result, six main categories, 13 subcomponents, and 107 indicators were identified. The extracted main categories include: information disclosure, core organizational values, intellectual ownership in the virtual world, governance competency, legal and regulatory structures, and financial and communication capability. Finally, in order to determine the causal relationships and hierarchies among the themes, Interpretive Structural Modeling (ISM) was employed. According to the results, the themes were distributed across five levels.